2015
DOI: 10.1007/s00701-015-2521-6
|View full text |Cite
|
Sign up to set email alerts
|

Brain arteriovenous malformations in elderly patients: clinical features and treatment outcome

Abstract: Brain AVMs in elderly patients still pose a high risk of hemorrhage. Initial hemorrhage may be associated with a history of hypertension, AVM size and exclusively deep venous drainage. Initial mRS score ≥2, eloquent location and higher S-M grade may be associated with worsening functional status. Microsurgical resection can be safe and effective for selected patients. Preoperative embolization is helpful in patients with S-M grade IV-V AVMs. For those with surgical contraindications, SRS and observation are tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…In the study by Yang et al., small size was associated with hemorrhagic presentation, with a reduction of 0.35 in the odds ratio (OR) for hemorrhagic risk every 1 cm increase in AVM size (OR = 0.65; P < 0.01). Fok et al., Tong et al . and Sahlein et al .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the study by Yang et al., small size was associated with hemorrhagic presentation, with a reduction of 0.35 in the odds ratio (OR) for hemorrhagic risk every 1 cm increase in AVM size (OR = 0.65; P < 0.01). Fok et al., Tong et al . and Sahlein et al .…”
Section: Discussionmentioning
confidence: 98%
“…The venous characteristics of AVMs have been widely evaluated and implicated in the hemorrhage of these lesions . The association between deep venous drainage and a higher incidence of hemorrhagic presentation was reported by several studies . Studies involving pediatric AVM patients found that deep venous drainage was associated with hemorrhagic presentation …”
Section: Discussionmentioning
confidence: 99%
“…Though most of the patients with AVM are young when diagnosis is made there are also patients becoming symptomatic only in older age, as in our case. A multicenter study [7] showed that 65% of all AVM of patients over 60 years were treated with microsurgery, supported by preoperative embolization in 1 out of 3 cases. Radiosurgery, embolization only, or a conservative approach was each chosen as therapy regimen in 10% of all cases.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is uncommon for AVMs to be first diagnosed late in life, such cases are possible. [7][8][9][10] Making a decision regarding AVM treatment for elderly patients is challenging due to the limited capacity for neurological recovery and increased general risk associated with surgery among this population, compared with younger patients. Supp-SM grading incorporates patient age into the scoring system and adds 3 points to the score for every AVM patient who is older than 40 years to adjust for this risk.…”
mentioning
confidence: 99%